Meningkatkan Mutu Pendidikan di SMP Islam Swasta - Nasrulloh, Moh. Eko (Universitas Al-Qolam Malang, 2025)
Achieving quality education is a fundamental goal for schools in providing educational services. Private schools, with their various limitations, face more complex challenges compared to public schools. Multiple strategies are required to improve the quality of education in private institutions. This study employs a qualitative method using a case study approach to uncover phenomena within the school environment. Interviews, observations, and documentation were used as data collection techniques. The results of the study indicate that school principals implement various strategies to enhance educational quality. These include competency development, providing motivation, and optimizing teachers' roles in various educational programs. Additionally, giving rewards to teachers to improve their performance is one of the efforts made to enhance educational quality.